PRODUCT INNOVATION ANALYSIS FOR DEVELOPING COMPETITIVE ADVANTAGE - Rosa Linda; Zianty Dwi Salza; Panji Agnyoto; Fajar Meiyanti (JABI (Journal of Accounting and Business Issues), 2021)
This study aims to analyze the product innovation process carried out by several coffee Micro, Small and Medium Enterprises (MSME)in developing competitive advantage. The research method used is a qualitative method using a descriptive approach. The data analyzed are the results of interviews with 3 coffee Micro, Small and Medium Enterprises (MSME)owners, 1 employee / barista and 1 customer from one of the coffee Micro, Small and Medium Enterprises (MSME). The result of this research is that the innovation process carried out by a company can provide added value that is not owned by its competitors, so that it can maintain its competitive advantage. The product innovation process carried out by several Micro, Small and Medium Enterprises (MSME) to maintain their competitive advantage is by conducting several product diversification so that customers do not feel bored with only a static menu. In addition, other innovations can be made by developing derivative products by modifying existing products.